Social Capital, Informal Governance, and Post-IPO Firm Performance: A Study of Chinese Entrepreneurial Firms - Cao, Xiaping (Jerry) (Journal of business ethics, 2016)
Social capital can serve as informal governance in weak investor-protection regimes. Using hand-collected data on entrepreneurs’ political connections and firm ownership, we construct several original measures of social capital and examine their effect on the performance of entrepreneurial firms in China after their initial public offerings. Political connections or a high percentage of external investors tend to enhance firm performance, but intragroup related-party transactions commonly lead to performance decline. These forms of social capital have a strong influence on the performance of Chinese firms, whereas formal governance variables such as board size or board independence have little effect. Although social capital may serve as an informal governance mechanism and effectively substitute for formal governance mechanisms in an emerging market, this role of social capital raises several ethical concerns, notably the development of rent-seeking and crony capitalism.